Intrinsic kinetic modeling with explicit radiation absoption effects of visible light-driven photocatalytic hydrogen production by water splitting using cadmium zinc sulfide in the presence of sulfide and sulfite - Tambago, Hyacinth Mae G.
Photocatalytic water splitting is an alternative method for the production of hydrogen, a clean energy carrier. Electron-hole recombination is a competing step and is minimized by adding sacrificial reagents to the photocatalytic system. Cadmium zinc sulfide is a photocatalyst active under visible light that is effective for hydrogen generation in the presence of sulfide and sulfite as sacrificial reagents. This is a promising system when waste streams containing sulfide and sulfite are utilized. Design of photocatalytic reactors to carry this process out requires the kinetic model for the photocatalytic reaction, which involves the absorption of photons. This study aims to investigate and develop a model for the intrinsic kinetics of hydrogen production using this system with explicit consideration of radiation absorption in the visible light region. The effect of catalyst loading, sulfide and sulfite concentration, and incident light intensity on the rate of hydrogen production on the cadmium zinc sulfide catalyst suspended in an externally irradiated batch reactor was investigated. The variation of the local volumetric rate of photon absorption (LVRPA) in the reactor was taken into account by modeling the radiation field in the reactor using the two-flux theory of Kubelka and Munk. A kinetic model reflecting the influence of sacrificial reagent concentrations and the LVRPA was developed and fit to the experimental data. The estimated model parameters are independent of irradiation form and reactor geometry and may thus be used to provide information for photocatalytic reactor design and scale-up.